IMPACT OF RELIGIOUS CRISIS IN 18 CENTURY ON DEPLOPMENT OF “MAGICAL REVIVAL” PROCESS IN FRANCE - Dmytro Pomazan (Київські історичні студії)
The purpose of the study is to unveil the religious crisis through the impact of the “Magical Revival” and esoteric secret organizations in France during the 18th century. The research methodology is based on the principles of historicism and scientific objectivity. In addition to general scientific methods such as analysis, synthesis, induction and deduction, special historical methods are used in the research: historical-comparative and historical-typological method, as well as for interdisciplinary sympathetic method was used for the complex study of esotericism as a religious component of society. The scientific novelty of the chosen question is in the formulation and development independent topic and holistic research problem. At the same time, in the historiography of the esoteric secret societies of Western Europe of modern times, the role of the religious crisis of the 18th century in the revival of “Magical revival” is not investigated. The analysed facts allow us to establish a clear link between the development of the 18th century religious crisis and the formation of esoteric secret societies in the context of the “Magical Revival” in the territory of nineteenth-century France. This is quite substantially demonstrated in the facts of anti-religious agitation and struggle, as well as in the context of increasing the number of occult organizations, as an alternative sacred form